Transculturation and Lorca's Syncretic 'Son de negros en Cuba': A 'gota de madera'. Issue 1 (2nd January 2021) - Silverman, Renée M.
Abstract : This essay examines how Federico García Lorca transforms the musical form son in his poem 'Son de negros en Cuba'. Significant in this is Lorca's relationship with anthropologist Fernando Ortiz, who regarded hybridity as foundational to post-colonial Cuban identity. For Ortiz and the Cuban writer Alejo Carpentier, son 's hybridity is analogous to ethnic and cultural syncretism, which Ortiz likens to counterpoint, or the juxtaposition of contrasting lines in music. Syncretism and counterpoint, the core concepts of Ortiz's theory of 'transculturation', become paradigmatic of Lorca's poem. By writing 'counterpoint' into the poem, Lorca creates space for the performance of intercultural dialogue.